A new trusteeship? the international administration of war-torn territories - Caplan, Richard (Adelphi paper, 2002)
This paper analyzes and assesses the effectiveness of international administrations of war-torn territories and discusses the key issues that arise in the context of these experiences. It reflects on the policy implications of these experiences and recommends reforms.